Pengembangan Ensiklopedia Jamur Makroskopis Sebagai Media Pembelajaran - Mardin, Herinda; H. Husain, Ilyas; D. Mamu, Hartono; Jumadil (Universitas Cokroaminoto Palopo, 2024)
The aim of this research is to test the feasibility of developing a macroscopic mushroom encyclopedia as a learning medium. This research is Research and Development (R&D) research. The research procedure adapted the ADDIE development model. The adaptation of the ADDIE model in this research was carried out at the encyclopedia validation stage. The encyclopedia validation test was carried out by two expert validators, namely a material expert validator and a media expert validator. Next, validators are asked to provide a general assessment and suggestions regarding the encyclopedia that has been developed, whether the encyclopedia is valid or invalid. Validation of the macroscopic fungal encyclopedia is in the very feasible category with a percentage of 92% by media expert validators and a percentage of 91% by material expert validators. The results of the validity test show the category is very feasible, which means that the resulting encyclopedia media does not need to be revised and is suitable for testing.